دور مواقع التواصل الإجتماعي في الترويج للصناعة التقليدية بمدينة الأغواط - خولة خليفي; د/حرزالله شوشة (جامعة عمار ثليجي الاغواط, 2023)
الملخص: نستخلص من هذه الدراسة أنالعملالارشاديمعالأفرادفيالمجتمعيحتاج إلىمجموعةمنالمهاراتالتييجبأنتتوافرفي المرشد الديني ليقومبإنجازهذاالعملبالشكلالمطلوب،ففيالمعتادانّالأفراديأتونالمرشد الدينيوفيتفكيرهم بعضالأهدافولديهمبعضالتصوراتولهذاينبغيأنيكونلدىالمرشدالدينيالقدرةعلىالتعرفعلى هذهالأهدافوتحديدمدىملائمتهاللعملية الارشادية، حيث ان أكثر اتصالاتنابالآخرينيتمعنطريق الكلمات، والباقيمنخلاللغةغيرمنطوقةتشمل: نغمةالصوت،ولغةالجسد،واسلوبالتعبيرعن المشاعر. الكلمات المفتاحية: الارشاد، الدين، المهارات، الاتصال Summary: We conclude from this study that the extension work with individuals in the community needs a set of skills that must be available in the religious guide to carry out this work as required. Religious is the ability to recognize these goals and determine their suitability for the counseling process, as most of our communication with others is done through words, and the rest is through non-verbal language that includes: tone of voice, body language, and the way of expressing feelings. Keywords: counseling, religion, skills, communication
دراسة حالة غرفة الصناعة التقليدية بمدينة الأغواط -الفيسبوك كنموذج-